A New Interpretation of the Human Embryo Drawings in Icones Embryonum Humanorum by Samuel Thomas Soemmerring - Godoy-Guzman, C (Springer, 2021)
In 1799, Samuel Thomas Soemmerring published the book Icones Embryonum Humanorum, which was one of the first attempts in history to sort out prenatal human development chronologically. Despite its importance for the anatomical sciences, there is little information about Icones. In this context, our objective was to identify and estimate the developmental age of the seven human embryos present in Icones Embryonum Humanorum by external morphological analysis and morphometry of the drawings using Image-J® software. First, the book was translated from Latin. Then, the developmental age was estimated by external morphological analysis and morphometry (greatest length) of the drawings using Image-J® software. The book is composed of 20 drawings of human embryos and fetuses from two life-size tables. According to the external features and morphometric analysis, there are seven embryos (drawings I–VII). The embryonic age (pf: post-fertilization age) of drawing I corresponds to day 29–31 pf; drawing II, to day 33–35 pf; drawing III, to day 37–40 pf; drawing IV, to day 42–45 pf; drawing V, to day 45–47 pf; drawing VI, today 47–50 pf; and drawing VII, to day 52–55 pf. There are differences between the development age estimated by Soemmerring and our analysis. These differences are probably due to the methodological and technical limitations of the eighteenth century. © 2021, Japanese Association of Anatomists.